Soji Project: Virtual Campaign And Distribution Of Hand Sanitizer From Local Commodities To Street Vendors - Asri Widyasanti; Angela A. Lasut; Fani R. Rahmani; M. Ridwan Rais; Nurhanifah Puspitadewi; Rangga Novandra (Universitas Serang Raya, 2021)
The SOJI project is one of activity dealing with community empowering and services with the topic